Sundry optical solitons and modulational instability in Sasa-Satsuma model - Justin, Mibaile; David, Vroumsia; Shahen, Nur Hasan Mahmud; Sylvere, Azakine Sindanne; Rezazadeh, Hadi; İnç, Mustafa; Doka, Serge Y. (Springer, 2022)
In this paper, we find new soliton solutions of the Sasa-Satsuma equation according to the Sardar sub-equation scheme. Different forms of soliton solutions, including the optical dark, optical bright, and optical singular function solutions are formally extracted. To better realize the physical phenomena of the gained solutions, some physical explanations of the exhibited solutions under suitable parameters for the physical values via the contour and 3D simulations are given. The confrontation between the dispersion and nonlinear terms has permitted survey the treatment of the Modulation Instability gain spectra.
Keywords: Sundry optical solitons; Modulational instability; Sasa-Satsuma model